Nursing experience of dressing change at home for a patient with heart failure complicated with pressure injuries (1例心力衰竭合并压力性损伤患者居家换药心得体会) - ZHANG Fengyao (张凤尧); HOU Pengxiao (侯朋晓); LIU Xueni (刘学妮); WANG Liangmin (王梁敏) (中西医结合护理)
This paper summarized the nursing experience of dressing change at home for a patient with heart failure complicated with pressure injuries. The nursing strategy included professional wound evaluation, dressing change, position management, health education, nutrition support, and blood sugar control through the management of lifestyle and diet, creating a good condition for wound healing. (本文总结1例心力衰竭合并压力性损伤患者的居家换药体会。通过规范的伤口评估与换药处理、患者体位管理、健康宣教、营养支持以及从生活习惯和饮食结构等方面进行血糖控制, 为创面愈合创造良好的条件。)